6(9z-12)=9(5z+11)

Simple and best practice solution for 6(9z-12)=9(5z+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(9z-12)=9(5z+11) equation:


Simplifying
6(9z + -12) = 9(5z + 11)

Reorder the terms:
6(-12 + 9z) = 9(5z + 11)
(-12 * 6 + 9z * 6) = 9(5z + 11)
(-72 + 54z) = 9(5z + 11)

Reorder the terms:
-72 + 54z = 9(11 + 5z)
-72 + 54z = (11 * 9 + 5z * 9)
-72 + 54z = (99 + 45z)

Solving
-72 + 54z = 99 + 45z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-45z' to each side of the equation.
-72 + 54z + -45z = 99 + 45z + -45z

Combine like terms: 54z + -45z = 9z
-72 + 9z = 99 + 45z + -45z

Combine like terms: 45z + -45z = 0
-72 + 9z = 99 + 0
-72 + 9z = 99

Add '72' to each side of the equation.
-72 + 72 + 9z = 99 + 72

Combine like terms: -72 + 72 = 0
0 + 9z = 99 + 72
9z = 99 + 72

Combine like terms: 99 + 72 = 171
9z = 171

Divide each side by '9'.
z = 19

Simplifying
z = 19

See similar equations:

| 2x+33?5x+6= | | 100x*10000=250x | | -6+4x+6x=-66 | | 4m-20=20-16m | | y=4x^3-.5x+2 | | 8c-120=240+5c | | 7x+8+4x=-80 | | x^4-20x^3+141x^2-406x+392*x-9=0 | | T(f+9)=40 | | 5y-7y=10 | | 6x-30=60-3x | | 9r-4=44+6r | | 5(2x+-7)-3(3x-10)+4= | | (D^3-D^2-4D-2)y=0 | | 46+16y=572 | | 4x-39=90 | | -17-20=-13x+80 | | 2x+3=9x+12-x | | 4x+2+6x=82 | | -5d+120=-6d-9 | | 8(3G+5R)= | | 14+29m=28+22m | | -8x-22=-3(x-1) | | 4x+17=90 | | 2f+20=101-f | | 2w-18w=-32 | | 32+12y=420 | | 78=3c+12+-1c+4 | | -139=5x+7+5 | | x-38=84 | | 3m+167=55+4m | | 12y+22=9y |

Equations solver categories